TENSEGRITY: CONFIGURAÇÕES GEOMÉTRICAS, SCRIPTS E PROTOTIPAGEM - NATACHA FIGUEIREDO MIRANDA (2024)
The work proposes to think about spatialities and structures that can be versatile, dynamic and efficient from a structural point of view, as well as, from a functional point of view, they can be coupled and connected to buildings, serve as temporary shelter, constitute pavilions etc., but with a focus on low-impact strategies in relation to the environment. Based on the notion of bioinspiration, such structures make it possible, like what happens in mammals in which a bionic system involving bones and tendons, to seek a metaphor in the sense of structural and spatial optimization, and as a consequence, to develop a project model with conception regenerative – the building collaborating with the natural phenomena of the place. Using contemporary design methods based on digital mediation, such as parameterization, prototyping and digital fabrication, the research will develop prototyping and analysis at various scales and materialities in order to assemble a Catalog with Tensegrities to disseminate knowledge and help beginners to use this structural system to design projects. Implantable or transformable structures will be considered for research, as they have an adaptable, modular and dynamic character, with Tensegrity being the structure chosen for this study. Keywords: digital architecture, regenerative architecture, parametric structures, deployable structures, Tensegrity.